Characteristics of the verbal lexicon in the Spanish of Amazonian bilingual indigenous people - Falcón Ccenta, Pedro Manuel (2012)
The development of the verbal lexis of Amazonian bilingual indigenous people is described from a lexical-semantic perspective, Ashaninka-Spanish and Shipibo- Spanish, in that order, according to the highest number of entries given by each of these populations. The morphologic and semantic characteristics of the verbal lexis used more recurrently are analyzed, which those evidence a big influence from Quechua and Andean Spanish.